ECOLOGY SAFETY – SUSTAINABLE DEVELOPMENT AND ECONOMICALASPECT - Zofia Szewczyk (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The aim of the research is to approximate ecological safety issues, sustainable development and investment outlaysfor environmental protection and water management. The article is a theoretical and empirical review. It has beenprepared using sources from GUS (polish Central Statistical Office). Analysis concern selected years from 2000 -2015.Investment outlays for environmental protection used by provinces and investor groups concern 2015. The followingresearch tools were used: review of literature, descriptive and comparative analysis. Investment outlays in environmentprotection and water management increased, but their part in investment outlays in the national economy is not toohigh. The most of outlays for environmental protection in 2015 was incurred in following provinces: Mazowieckie,Wielkopolska and Śląskie, while the least in Warmińsko-Mazurskie and Podlaskie. The structure of investor groupsfor environmental protection has not changed for several years. The main investors are the companies (whose part inexpenditures in this year was 67%), the next commune (27%), then the budget units (6%).